Analisis strategi, tantangan dan implementasi pemasaran produk cicil emas oleh BSI KCP Lumajang S. Parman: Solusi investasi syariah dalam membangun kepercayaan dan kepuasan nasabah - -, Farah Salsabila (Maliki Interdisciplinary Journal, 2025)
The development of Islamic finance in Indonesia has encouraged innovative products, one of which is Cicil Emas marketed by Bank Syariah Indonesia (BSI). This study analyzes the marketing strategy, challenges, and implementation of Cicil Emas at BSI KCP Lumajang S. Parman using the marketing mix (7P) and field observations. The results show that the strategy involves a murābaḥah-based scheme, transparent pricing, educational promotion, and digital services. Key challenges include gold price fluctuations, low literacy, competition, and internal limitations. Implementation is carried out adaptively through continuous education, community collaboration, and risk management. Cicil Emas is proven to be not only a financing instrument but also a sharia investment solution that enhances trust, satisfaction, and financial inclusion.